Big Data Peran Big Data Dalam Sistem Informasi Management Untuk Mendukung Keputusan Strategis Di E-Comerce: Peran Big Data Dalam Sistem Informasi Management Untuk Mendukung Keputusan Strategis Di E-Comerce - Siregar, Petrus Kabul Swastadi; Faeni, Dewi Puspaningtyas (Jurnal Bisnis Administrasi dan Manajemen, 2025)
This study aims to analyze the role of big data in management information systems (MIS) to support strategic decision-making in the e-commerce sector. The approach used is a narrative literature review with reference to various national and international scientific journals published in the period 2015–2025. The analysis was conducted using Mendeley software for reference management and NVivo for thematic analysis based on TOE and RBV theories. The results show that the integration of big data into MIS enables e-commerce organizations to conduct customer behavior analysis, inventory optimization, and more accurate and adaptive prediction-based strategic planning. This study also identifies various implementation challenges, including issues of data quality, privacy, and infrastructure readiness. This study concludes that the utilization of big data is a key factor in increasing the effectiveness of strategic decisions and competitive advantage. The main limitation of this study is the lack of empirical validation of the findings obtained. This study contributes to the development of data-driven business strategies, both at the level of e-commerce industry practitioners and in the fields of information systems and strategic management studies.